Ascertainment of Customs and Personal Laws in Medieval Italy from the Lombard Kingdom to the Communes - Claudia Storti (Rechtsgeschichte - Legal History, 2016)
The medieval systems of law in Italy and Europe have been proposed as a sort of virtual laboratory to deal with the issue of ensuring that the principle of equality in the rule of law be compatible with the recognition of indigenous peoples’ customs. The legal framework of the medieval communes sought to strike a balance between the general interest in having legal certainty and uniformity with the citizens’ interest in ruling their family life and economic assets according to their cultural and social values. Up until the 14th century, in Lombardy an individual’s legal status, family and inheritance continued to be ruled according to the customs of the individual’s natio, be they Lombard or Roman. The ascertainment of customs is an arduous task, as oral customs are ﬂuid and vary from place to place and from family to family. For this reason, in the Middle Ages ascertainment was always entrusted to judges and legal experts (sapientes). Until a few decades ago, recognising and enforcing customs was mostly unthinkable due to legal positivism and the principle of equality. Now, however, the limits of the principle of legal equality are well known: »Legal positivism was not able to abolish status« (G. Alpa). The recognition of »legal Indigenous status« provides continuity between the past (the Middle Ages) and present (Indigenous Peoples Basic Law). Just as in the past, when living according to a given natio’s laws and customs did not mean self-government, so today the enforcement of an indigenous peoples’ basic law should not undermine the sovereignty of the State.